SOSIALISASI PENYEBAB DAN DAMPAK AKIBAT PENURUNAN MUKA TANAH (LAND SUBSIDENCE) DI KELURAHAN TANJUNG MAS SEMARANG - Agus Muldiyanto,; Adolf Situmorang,; Edy Susilo, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The coastal part of Semarang City is generally formed from alluvial deposits, which have rock structure characteristics that are still undergoing a consolidation process, this is one of the causes of land subsidence, besides that it is influenced by other factors, namely groundwater extraction by means of deep wells (artetist), the effect of the burden, the effect of global climate change. The service team conducted outreach to the community in RW 12, Tanjung Mas Village, North Semarang, Semarang City about the causes of land subsidence, the impact and how to overcome it, as well as community participation in assisting the government. With this service, it is hoped that the community in the Tanjung Mas Village area can participate and assist in preventing/reducing and overcoming and monitoring, especially the causes and impacts of land subsidence. The method used in this socialization includes providing hardcopy material, explaining the material, and discussing the content of the material. After the socialization was held, the understanding of the people in the area increased from 60% to 80%.